DEEP LEARNING: TRANSFORMASI PARADIGMA MENUJU PEMBELAJARAN BERMAKNA DAN KARAKTER UNGGUL - Mukti Abam, Indra; Asmiranda; Wigati, Indah; Yuniar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the deep learning policy as a new approach in transforming the educational paradigm. The method used is a literature review that explores the definition, objectives, framework, and practical implementation of deep learning in the context of education. The results of the discussion indicate that in the world of education, deep learning is an approach that emphasizes genuine conceptual understanding, rather than mere memorization, in order to develop students' critical and creative thinking skills. The main focus of this approach encompasses three aspects: mindful learning, meaningful learning, and joyful learning. The implementation of this policy requires synergy between active pedagogical practices, inclusive learning environments, utilization of digital technology, and strong partnerships among schools, parents, and the community. The conclusion of this paper affirms that deep learning serves as an important foundation for shaping a generation with strong character, such as honesty and empathy, as well as competencies that are relevant in facing future global challenges.